2011
DOI: 10.4049/jimmunol.1003748
|View full text |Cite
|
Sign up to set email alerts
|

Invariant NKT Cell Reconstitution in Pediatric Leukemia Patients Given HLA-Haploidentical Stem Cell Transplantation Defines Distinct CD4+ and CD4− Subset Dynamics and Correlates with Remission State

Abstract: Immune reconstitution plays a crucial role on the outcome of patients given T cell-depleted HLA-haploidentical hematopoietic stem cell transplantation (hHSCT) for hematological malignancies. CD1d-restricted invariant NKT (iNKT) cells are innate-like, lipid-reactive T lymphocytes controlling infections, cancer, and autoimmunity. Adult mature iNKT cells are divided in two functionally distinct CD4+ and CD4− subsets that express the NK receptor CD161 and derive from thymic CD4+CD161− precursors. We investigated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 48 publications
6
63
0
Order By: Relevance
“…48,49 Consistent with these findings, a recent report demonstrated that reconstitution of NKT cells in peripheral blood is associated with long-term remission of pediatric leukemia patients receiving haploidentical transplantation. 50,51 Overall, our results provide the rationale for the development of an NKT-cell-based platform for CAR-directed cancer immunotherapy that could be applied to a broad range of malignancies and used in either autologous or allogeneic settings.…”
Section: Discussionmentioning
confidence: 81%
“…48,49 Consistent with these findings, a recent report demonstrated that reconstitution of NKT cells in peripheral blood is associated with long-term remission of pediatric leukemia patients receiving haploidentical transplantation. 50,51 Overall, our results provide the rationale for the development of an NKT-cell-based platform for CAR-directed cancer immunotherapy that could be applied to a broad range of malignancies and used in either autologous or allogeneic settings.…”
Section: Discussionmentioning
confidence: 81%
“…32 In the setting of allo-SCT, de Lalla et al reported that after ex vivo T cell-depleted pediatric haploidentical allo-SCT, iNKT reconstitution was associated with sustained disease remission. 37 Finally, in the study of Rubio et al, patients with a higher iNKT/T-cell ratio showed a trend toward a lower risk of relapse. 21 Together with the current study, these data suggest an antitumor effect of donor-derived iNKTs after allo-SCT.…”
Section: Discussionmentioning
confidence: 99%
“…As reported in this study, Foxp3 + iNKT cells can suppress both autologous and heterologous CD4 + T cells, suggesting that these cells could contribute to controlling exacerbated inflammatory responses and to autoimmunity, but also to the expansion of heterologous cells as in the case of graft-versus-host disease. In support of this notion, several studies have provided evidence for a role of iNKT cells in promoting or maintaining tolerance in a variety of experimental graft-versus-host disease or autoimmune disorders (18,19,(48)(49)(50)(51)(52). The mechanisms accounting for their tolerogenic effects are still unclear but they were shown to be independent from IL-4 and IL-10 in autoimmune diabetes (53).…”
Section: Discussionmentioning
confidence: 98%